NUTRITIONAL HEALTH IN EARLY CHILDHOOD IN RA DDI MAJENNANG, SUPPA DISTRICT, PINRANG REGENCY - Ika Mustika Harun; Lenny Kusmiran; Halijah; Kasma; Maswati (PT. Jurnal Center Indonesia Publisher, 2025)
Nutrition health in early childhood plays an essential role in supporting optimal growth and development. This study aims to determine the nutritional status of children at RA DDI Majennang, Suppa District, Pinrang Regency, and the factors influencing it. The research used a descriptive method with observation and interviews involving teachers and parents. The results showed that most children had good nutritional status, although some experienced undernutrition due to unbalanced diets and limited parental knowledge about nutrition. The main factors influencing children’s nutritional status included parents’ knowledge level, family income, and frequent consumption of fast food. These findings highlight the importance of providing nutrition education for parents and fostering cooperation between schools and families to improve the nutritional health of early childhood students at RA DDI Majennang.